2016
DOI: 10.1007/s11524-016-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Unprotected Sex and Unplanned Pregnancy among Urban African-American Adolescent Girls Using the Theory of Gender and Power

Abstract: Reproductive coercion has been hypothesized as a cause of unprotected sex and unplanned pregnancies, but research has focused on a narrow set of potential sources of reproductive coercion. We identified and evaluated eight potential sources of reproductive coercion from the Theory of Gender and Power including economic inequality between adolescent girls and their boyfriends, cohabitation, and age differences. The sample comprised sexually active African-American female adolescents, ages 15-21. At baseline (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
(45 reference statements)
0
20
2
Order By: Relevance
“…However, they found that only participants who experienced RC were at increased risk of UIP. Rosenbaum, Zenilman, Rose, Wingood, and DiClemente (2016) found that young African American women of low socioeconomic status who cohabitated with abusive partners were significantly more likely to report RC and UIP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, they found that only participants who experienced RC were at increased risk of UIP. Rosenbaum, Zenilman, Rose, Wingood, and DiClemente (2016) found that young African American women of low socioeconomic status who cohabitated with abusive partners were significantly more likely to report RC and UIP.…”
Section: Discussionmentioning
confidence: 90%
“…First, IPV in PRAMS is limited to physical abuse only. However, physical abuse as opposed to other forms of abuse is most commonly associated with RC and UIP Rosenbaum et al, 2016). Furthermore, the assessment of RC in PRAMS is limited to birth control sabotage.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of the data held by a statewide counselling service in Queensland, Australia, Price et al (2019) found a 21 per cent co-occurrence of RC and other forms of DV in Queensland women experiencing an unplanned pregnancy. International population estimates place the prevalence of co-occurring RC and other forms of DV at between 9 and 40 per cent depending on the population studied (Black et al 2010;Clark et al 2014;McCauley et al 2014;Miller and Silverman 2010;Moore, Frohwirth and Miller 2010;Nikolajski et al 2015;Rosenbaum et al 2016;Silverman and Raj 2014). In an American study, Fleury-Steiner and Miller (2019) interviewed 172 women shortly after a DV protection order hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in addition to gender role and dominance, economic dependence also significantly contributes to increased risky sexual behaviors. For example, in a study conducted by Rosenbaum et al, women who were economically dependent on their dominant male partners were exposed to relatively higher levels of unprotected sex (Rosenbaum, Zenilman, Rose, Wingood, & DiClemente, 2016).…”
Section: Discussionmentioning
confidence: 99%